PERAN KEPUASAN KERJA DAN WORK ENGAGEMENT DALAM MEMEDIASI PENGARUH DUKUNGAN ORGANISASI DAN KOMPENSASI TERHADAP KINERJA GURU SEKOLAH DASAR - Robiatul Adhawiyah, Isna; Yanto, Heri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teacher performance is a key factor in determining the success of educational implementation, influenced by organizational and individual psychological factors. Organizational support and compensation are considered external factors that shape teachers’ working conditions, while job satisfaction and work engagement reflect internal psychological conditions that affect the quality of teachers’ professional duties. This study aims to analyze the roles of job satisfaction and work engagement in mediating the effects of organizational support and compensation on elementary school teachers’ performance. This study employed a quantitative approach using a survey method. The research population consisted of 4,239 public elementary school teachers in Kendal Regency, with a sample of 376 teachers selected using the Slovin formula through random sampling. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling (SEM) with the assistance of AMOS version 26. The results show that organizational support has a positive and significant effect on teacher performance, while compensation does not have a significant direct effect. Work engagement also has a positive and significant effect on teacher performance. Mediation analysis indicates that work engagement mediates the effects of organizational support and compensation on teacher performance. Moreover, job satisfaction and work engagement sequentially mediate the effect of organizational support on teacher performance partially, and fully mediate the effect of compensation on teacher performance. This study highlights that improving teacher performance requires strengthening organizational support, implementing fair compensation systems, and creating a conducive work environment that enhances teachers’ job satisfaction and work engagement sustainably.